Desencontros entre planejamento e controle na implementação de políticas públicas: análise do PPA 2016-2019 do estado de Goiás e o controle de contas - Gomes, Vera Núbia Zandonadi (2020)
The theoretical and empirical study finds that the budget system in the constitutional and infra-constitutional context is, in its abstract design, sufficient to develop in responsible financial planning, but it is still used inefficiently. The research investigates, using a case study approach methodology and qualitative quantitative analysis procedures, whether the PPA 2016-2019 in the State of Goiás can be considered an effective planning tool in controlling the execution of public policies, an analysis carried out intertwining the nuances of LDO's and LOA's from the same period. Execution flaws are noted, such as: low adherence to what was planned; excess commitment cancellation; discrepancy between programs by area; actions marked as priority with zero or very low level of execution. It demonstrates how the control of public policies is on the national scene, especially by the Courts of Accounts, certifies that they contribute to the consolidation of the democratic rule of law. It verifies the panorama of public policy control by the TCE-GO, in the same timeframe, in relation to the PPA programs object of the case. The situation highlights the need for the control body to exercise its noble constitutional mandate with greater diligence. In view of the detected scenario, a “Systematic Monitoring of the Current PPA” panel proposes, based on good governance, working in a systematic way, providing data that allow directions for control actions with areas of greater risk, generating greater value for society in guaranteeing fundamental rights.